Women’s Citizenship Practices and Social Power Dynamics in Blitar Regency’s Community Development Programs - Krisno Wicaksono, Yudi; Atirotu Zahroh, Luluk; Nabihah, Tengku Izzati; Raman, Asrul; Zahro Al Istiqlaliyah, Alfiatuz (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
This study explores women's citizenship practices and their role in shaping social power dynamics within community-based development programs in Blitar Regency, East Java. Focusing on the KOTAKU (City Without Slums) and Desa/Kelurahan Berseri (Radiant Village) programs, the research examines how women contribute to inclusive and sustainable development through active participation in both planning and implementation stages. Using a qualitative case study approach, data was gathered through in-depth interviews, field observations, and document analysis. Findings indicate that women participated in the rembug (community consultation) stage, voicing needs and shaping development priorities. This early engagement enabled more inclusive and representative decision-making. During program implementation, women provided vital logistical support, such as preparing meals and refreshments for workers, demonstrating care, ownership, and solidarity. These roles, though often perceived as informal, were integral to program success and reflect meaningful expressions of civic agency. The study argues that recognizing women’s contributions—both strategic and supportive—is essential to redistributing social power and fostering gender equity. By highlighting women’s active citizenship, this research contributes to a deeper understanding of how gender-inclusive development initiatives can transform community structures and promote more equitable and democratic outcomes.